My Data Are Ready, How Do I Analyze Them: Navigating Data Analysis in Social Science Research - Fodouop Kouam, Arthur William (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper offers a practical guide for researchers to effectively analyze their data in social science research, addressing the challenges and pitfalls commonly encountered in data analysis. By exploring various data analysis techniques, highlighting key challenges such as data quality issues and statistical assumptions violations, and providing practical tips and guidelines, this study fills a gap in the existing literature by offering a comprehensive approach to navigating data analysis in social science research. The significance of this study lies in its potential to improve the quality and reliability of research findings in the social sciences, equipping researchers with the necessary knowledge and skills to conduct robust data analysis. This study is a valuable resource for researchers seeking to enhance their analytical skills, avoid common pitfalls, and advance knowledge in their field of study.